THE ROLE OF COMPUTER ASSISTED LANGUAGE LEARNING (CALL) IN TEACHING LANGUAGES - Saidazimova Farog'at (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Globalization has made technology a key source of information and not only a tool for education. Similarly, language is seen as a source of knowledge and information in addition to being used for communication. The modern generation now relies heavily on computers in their daily lives. They feel far more at ease using computer technology to learn than they do with more conventional methods. Keeping this in mind makes using computer technology for teaching and learning more successful. Computer-assisted language learning, or CALL, is bringing about a revolution in the field of language teaching. The field of language education is undergoing a revolution as a result of computer-assisted language learning, also known as CALL.